W co wierzy pokolenie Z? Transformacje religijności cyfrowej młodzieży - Drozdowicz, Jarema (Przegla̜d religioznawczy, 2022)
This article delivers an analysis of the most important aspects of the effect the generational change makes in shifts in religiosity and spirituality among the youth groups. Especially the so called generation Z seems interesting and significant in that regard. The characteristics of that group show that the most important factor we must include in the interpretation of data on religion is related to the consequences of the technological and cultural transformation that occurs today globally. Thus the text emphasizes the relations between the digital realm and new religiosity of youth in fields like worldview, work or everyday habits. The perspective of sociology and anthropology of religion used here allows us to take a closer look at the latest currents in youth religiosity. The outcome of that analysis shows that it is crucial to take into consideration the fact that this religiosity is today regarded in a more personalistic but at the same time socially and politcally engaged manner.